Analysis of Reservoir Water Discharge at Solar Power Plant Tanjung Raja Village as a Basis for Pico Hydro Power Plant Planning in Paddy-Field Area - Dinata, Yogi; Indriyani, Indriyani; Dewi, Tresna (International Journal of Advanced Science Computing and Engineering, 2022)
Energy is an important aspect of life as a whole. The fossil-based energy sources have dwindled over time, in line with population growth and economic growth. One approach to meeting the energy demand is to use renewable energy. According to Presidential Regulation Number 22 of 2017 on National Energy General Plan (RUEN) targets, the share of New and Renewable Energy in total national energy in 2025 will be 25%. The construction of a Hydro Power Plant is expected to reach 3.000 MW by 2025. According to NREEC statistical data from 2016, the potential for constructing a Hydro Power Plant in South Sumatera is approximately 448 MW. This paper investigates the possibility and potential of building Hydro Power Plant from the reservoir of the irrigation water system generated by a Solar Power Plant in Tanjung Raja Village, Muara Enim District, South Sumatra. The water discharge magnitude is measured, and the potential of electricity generated from the discharge is presented. The experimental data shows that water discharge from the reservoir can generate maximum electricity ofÂ  806,6488 watts with a discharge rate of 0.0653 m3/s, and power is 36,7245 watts, with a discharge of 0,0030 m3/s. The average electricity potential is approximately 375.6782 watts, with a discharge average of 0.0304 m3/s. Therefore, the experimental data shows the possibility of hybridizing the Solar Power Plant with Hydro Power Plant, which will be beneficial for the residential area in Tanjung Raja Village, Muara Enim.